Strategic Capability: A Concept And Framework for Analysis - Lenz, R. T. (Academy of Management Review, 1980)
The central purpose of this paper is to identify a concept and an analytical framework for evaluating the capability of an organization to undertake strategic action. Implications for theory building and practical application are discussed.